2019
DOI: 10.1177/2309499019843407
|View full text |Cite
|
Sign up to set email alerts
|

Spinal fractures in diffuse idiopathic skeletal hyperostosis: Advantages of percutaneous pedicle screw fixation

Abstract: To validate the effectiveness of percutaneous pedicle screw (PPS) fixation for spinal fractures associated with diffuse idiopathic skeletal hyperostosis (DISH) by comparing surgical outcomes for PPS fixation and conventional open posterior fixation. Patients with DISH are vulnerable to unstable spinal fractures caused by trivial trauma, and these fractures have high rates of delayed paralysis, postoperative complications, and mortality. Methods: This retrospective study assessed surgical outcomes for 16 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
(78 reference statements)
0
26
0
Order By: Relevance
“…Lindtner et al 28 compared six patients in MISt group and 14 patients in open group and found that the open group had higher post-operative complication rate (1.3 vs. 0.7 complications per patient). Okada et al 29 , in a retrospective review comparing 16 DISH patients undergoing MISt and 25 DISH patients undergoing conventional open surgery for spinal fractures, reported shorter operation duration and lower blood loss in the MISt group. Three patients in the open surgery group succumbed to death due to hypovolemic shock, respiratory failure and pneumonia, within a year of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lindtner et al 28 compared six patients in MISt group and 14 patients in open group and found that the open group had higher post-operative complication rate (1.3 vs. 0.7 complications per patient). Okada et al 29 , in a retrospective review comparing 16 DISH patients undergoing MISt and 25 DISH patients undergoing conventional open surgery for spinal fractures, reported shorter operation duration and lower blood loss in the MISt group. Three patients in the open surgery group succumbed to death due to hypovolemic shock, respiratory failure and pneumonia, within a year of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all the postoperative CT images were obtained on postoperative day 2 before the patients started to mobilize, meaning that screw pull-out is most likely to occur during the operation. Other studies also mentioned that pedicle screw pull-out occurs during rod connection [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…In long instrumented fusion in particular, pedicle screw pull-out was found to be a risk factor for pedicle screw loosening [10]. It has been reported that pedicle screw pull-out can occur during, but not after, surgery [10,11]. Aprevious study investigatedpercutaneous pedicle screw (PPS) pull-out during rod reduction and reported its association with screw loosening.…”
Section: Introductionmentioning
confidence: 99%